2018
DOI: 10.1186/s12890-018-0573-0
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbations and healthcare resource utilization among COPD patients in a Swedish registry-based nation-wide study

Abstract: BackgroundExacerbations of chronic obstructive pulmonary disease (COPD) are an important measure of disease severity in terms of impaired disease progression, increased recovery time, healthcare resource utilization, overall morbidity and mortality. We aimed to quantify exacerbation and healthcare resource utilization rates among COPD patients in Sweden with respect to baseline treatments, exacerbation history, and comorbidities.MethodsPatients with a COPD or chronic bronchitis (CB) diagnosis in secondary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…COPD places a significant burden on patients and healthcare systems,2,11 and exacerbations, in particular, impose a significant burden, accounting for the majority of hospital admissions for patients with COPD 12,13. Health care resource utilization (HCRU) is measured in registry-based studies by hospitalizations and out-patient visits in order to describe the burden of the disease 14. A study based on registry data from Sweden demonstrated that patients with a history of severe exacerbations and high use of medication for COPD had an increased rate of exacerbations and HCRU 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD places a significant burden on patients and healthcare systems,2,11 and exacerbations, in particular, impose a significant burden, accounting for the majority of hospital admissions for patients with COPD 12,13. Health care resource utilization (HCRU) is measured in registry-based studies by hospitalizations and out-patient visits in order to describe the burden of the disease 14. A study based on registry data from Sweden demonstrated that patients with a history of severe exacerbations and high use of medication for COPD had an increased rate of exacerbations and HCRU 14.…”
Section: Introductionmentioning
confidence: 99%
“…Health care resource utilization (HCRU) is measured in registry-based studies by hospitalizations and out-patient visits in order to describe the burden of the disease 14. A study based on registry data from Sweden demonstrated that patients with a history of severe exacerbations and high use of medication for COPD had an increased rate of exacerbations and HCRU 14. As a result, the economic burden of the disease is substantial, and given the ageing populations in many countries, it is likely to continue to rise over time.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that comorbidities increase the risk for exacerbations and hospitalizations, reduce health status, and increase the risk of mortality in COPD patients. 4 11 Various comorbidities studied in patients with COPD include asthma; lung cancer; cardiovascular diseases, such as heart failure, ischemic heart disease, arrhythmias, peripheral vascular disease, and hypertension; osteoporosis; depression; anxiety; metabolic syndrome and diabetes; gastroesophageal reflux; bronchiectasis; and obstructive sleep apnea. 3 , 5 , 8 , 12 16 …”
Section: Introductionmentioning
confidence: 99%
“…The overall readmission rate was 14%. The Swedish National study [21] found that among the 88,548 patients with COPD, CCI of female patients was (mean 2.5 ± 1.9), and of male patients was (mean 2.9 ± 2.1) (p < 0.001). The overall mean (SD) CCI score was 2.7 ± 2.0.…”
Section: Discussionmentioning
confidence: 97%